Literacy Culture in Islamic Boarding Schools: The Relationship Between Free Time and the Reading and Writing Motivation of Students at the Hidayatus Sholihin Islamic Boarding School in Wringinjajar, Mranggen, Demak - Choeroni Choeroni; Khoirul Anwar (Universitas Islam Sultan Agung, 2026)
Literacy culture is an essential element in developing the intellectual tradition within Islamic boarding schools (pesantren). The productive use of leisure time is considered to contribute to strengthening literacy culture while enhancing students' reading and writing motivation. This study aims to describe the literacy culture developed at Pondok Pesantren Hidayatus Sholihin Wringinjajar Mranggen Demak, analyze how students utilize their leisure time for literacy activities, and examine the impact of leisure time utilization on students' reading and writing motivation. This study employed a qualitative field research approach. Data were collected through observation, in-depth interviews, and documentation involving the boarding school leader, teachers, library manager, and students. Data were analyzed using an interactive analysis model consisting of data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings reveal that literacy culture is fostered through habitual reading of classical Islamic texts, supporting books, group discussions, lesson reviews, and note-taking activities within a conducive learning environment. Students productively utilize their leisure time for various literacy activities, making it an integral part of their independent learning strategies. The productive use of leisure time positively influences students' reading and writing motivation, as reflected in increased reading interest, improved writing skills, active participation in discussions, and stronger independent learning habits. This study concludes that optimizing students' leisure time is a significant factor in strengthening literacy culture and enhancing reading and writing motivation in Islamic boarding schools.